Influence of Rangeland Land Cover on Infiltration Rates, Field-Saturated Hydraulic Conductivity, and Soil Water Repellency in Southern Patagonia - Hervé Fernandez, Pedro Alejandro; Muñoz Arriagada, Rene Santiago; Glucevic-Almonacid, C.; Bahamonde-Vidal, L.; Radic Schilling, Sergio Javier (My University, 2023)
This study investigated the influence of rangeland land cover on infiltration rates (IRs), field-saturated hydraulic conductivity (Kfs), and soil water repellency in Patagonia. Four land cover types (shrubs, dwarf heath shrubs, bare soil, and Inter tussock) were examined to assess their effects on hydrological pro-cesses. IR was measured using the single-ring method, and soil water repellency was evaluated using the Beerkan method. We hypothesized that land cover type affects IR, Kfs, and soil water repellency. The results showed significant variations in IRs among land covers, with Tsf displaying lower rates than the other covers. Soil water repellency was prevalent in shrub and dwarf heath shrub -covered soils. Lateral flow was observed, indicating limited water infiltration. The obtained Kfs values were higher than the calculated hydraulic conductivity values (Ks). However, further investigation is required to assess the im-pact of capillarity (i.e.,α*) on Kfs determination. This study enhances our understanding of hydrological processes in rangeland ecosystems and provides valuable insight into land management practices. By elu-cidating the relationships among land cover, IR, Kfs, and soil water repellency, this study contributes to sustainable water resource management in arid and semiarid regions.© 2023 The Authors. Published by Elsevier Inc. on behalf of The Society for Range Management. This is an open access article under the CC BY license ( http://creativecommons.org/licenses/by/4.0/ )
Keywords: field-saturated hydraulic conductivity; infiltration rates; land cover; rangeland; soil water repellency; southern patagonia